Empowering Rural Livelihoods Through Bali Cattle Development in Tambrauw Regency West Papua - Stepanus Pakage; Hengki Wabia; Mulyadi Mulyadi (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2026)
This study aims to develop alternative strategies for the advancement of the Bali cattle industry in Tambrauw Regency through the identification of critical internal and external factors influencing its growth. The research was conducted over a two-month period employing a descriptive approach, with data collection facilitated through quota, purposive, and cluster sampling techniques. Analytical tools utilized include the SWOT (Strengths, Weaknesses, Opportunities, and Threats) framework and the Quantitative Strategic Planning Matrix (QSPM). The analysis identified effective marketing mechanisms as the principal internal strength of the local cattle industry, while limited access to capital emerged as a primary internal constraint. From an external perspective, supportive government policies were recognized as key opportunities, whereas livestock theft and poaching constituted significant threats to industry sustainability. Strategic priorities derived from the SWOT-QSPM analysis encompass capital reinforcement, enhancement of production quality and quantity, improved access to markets and information, development of livestock production systems based on local resources, and institutional capacity building through strengthened collaborative networks and human resource development. The recommended strategic alternatives include increasing access to financial resources, expanding business operations, and improving production efficiency. These strategies are expected to contribute to the sustainable development of the Bali cattle industry in Tambrauw Regency.